A new perspective on a fundamental debate: a multilevel approach to industry, corporate, and business unit effects - Misangyi, Vilmos F.; Elms, Heather; Greckhamer, Thomas; Lepine, Jeffrey A. (Strategic Management Journal, 2006)
Abstract We utilized a multilevel approach to both estimate the relative importance of industry, corporate, and business segment effects on firm performance, as well as to demonstrate how it enables the investigation of specific strategic factors within each class of effects. Our results confirmed previous findings suggesting that although business segment effects carry the most relative importance, industry and corporate effects are also important. Among the findings regarding specific factors, we found that industry concentration and munificence, as well as the resource environment provided by corporate parents, impact performance. These findings suggest that investigators should consider both industry and corporate environments when examining performance. Copyright © 2006 John Wiley & Sons, Ltd.